Does pyrethroid exposure lower human semen quality? a systematic review and meta-analysis - Akhigbe, Roland Eghoghosoa; Oyedokun, Precious Adeoye; Akhigbe, Tunmise Maryanne; Adenike, Suliat; Oladipo, Ayoola Abimbola; Hughes, Jennifer Rose (Frontiers in Toxicology, 2024)
Background: Pyrethroids are natural organic compounds extracted from flowers of pyrethrums and commonly used as domestic and commercial insecticides. Although it is effective in insect and parasitic control, its associated toxicity, including spermotoxicity, remains a challenge globally. Currently, the available reports on the effect of pyrethroids on semen quality are conflicting, hence an evaluation of its detrimental effect is pertinent. This study conducts a detailed systematic review and meta-analysis of the effects of pyrethroids on sperm quality.Materials and methods. The present study was performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Using a pre-defined strategic protocol, an internet search was done using combined text words. The criteria for eligibility were selected based on Population, Exposure, Comparator, Outcome, and Study Designs (PECO) framework, and relevant data were collected. Appraisal was done using The Office of Health Assessment and Translation (OHAT) tool for the evaluation of the Risk of Bias and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) Working Group guidelines for the certainty of evidence. A quantitative meta-analysis was conducted with the Review Manager (RevMan). Results: Only 12 out of the 4, 050 studies screened were eligible for inclusion in this study. The eligible studies were from China (4), Japan (3), Poland (3), and USA (2). All the eligible studies were cross-sectional. A total of 2, 050 male subjects were included in the meta-analysis. Pyrethroid exposure significantly reduced sperm motility. Region-stratified subgroup analyses revealed that pyrethroid significantly reduced sperm motility among men in Poland and USA, and decreased sperm count among men in Japan. Pyrethroid exposure also reduced sperm concentration among men in Poland but increased sperm concentration among men in the USA. Conclusion: Although the study revealed inconsistent evidence on the detrimental effect of pyrethroids on semen quality, the findings showed that pyrethroids have deleterious potentials on sperm motility, count, and concentration. Studies focusing on the assessment of semen quality in pyrethroid-exposed men, especially at specific varying levels of exposure, and employing prospective cohort studies or controlled cross-sectional designs are recommended.